Coarse Particle Motion Characteristics in a Double-Stage Slurry Pump Considering Leakage Flow. (28th October 2021) - Jia, Hao; Wang, Yuqi; Zhu, Zuchao; Su, Xianghui; Tang, Zhenji
Abstract : Along with the pressing demand for the long-distance transportation of coarse particles in the deep-sea mining industry, evaluating the slurry pump's passing through and erosive wear by studying the particle motion characteristics and the slurry behavior is becoming increasingly important. Research on the influence of leakage flow through the clearance and balancing devices on the motion characteristic of granular grain flow is of great significance but has been seldom studied. This study coupled the discrete element method with the CFD method to investigate the comprehensive effect of a double-stage slurry pump's main flow and leakage flow on the motion characteristics of particles with a 10 mm diameter. Results show that the leakage flow occupation in main flow falls from 26%–27% to 8%–9% for the two stages, with the flow rate increasing from 80 m 3 /h to 200 m 3 /h. In the first stage with leakage, accumulation of coarse particles was observed at the impeller eye, which should be paid much attention to slurry pumps' operation to eliminate the chance of blockage. In the nonleak situation, although the increment of the average kinetic energy of particles through the impeller is more significant than in the leak case, most of them dissipate primarily by more than 10% collision in the bowl diffuser. In the leak or nonleak case, the average kinetic energy of particles was more than twice through the first stage but only 1.1 times through the second stage. The selection of stages in the slurry pump design should consider the limitation of particle velocity improvement.